2022
DOI: 10.1186/s12934-022-01769-6
|View full text |Cite
|
Sign up to set email alerts
|

Assess the diversity of gut microbiota among healthy adults for forensic application

Abstract: Background Human gut microbiota is individually unique that hints the microbiota in fecal traces left in the crime scene could act as a potential biomarker for forensic personal identification. Next-generation DNA sequencing and bioinformatic analysis of fecal samples are revolutionizing our insights into gut microbial communities. While the formation of the gut microbiota is known to be multifactorial, it is unclear whether these characteristics can be applied to forensic applications. Therefo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Studies have demonstrated that gut microbiota can be used to reflect age-related and sex-related changes, helping to roughly identify sexes and different age groups (de la Cuesta-Zuluaga et al, 2019 ; Takagi et al, 2019 ; Huang et al, 2020 ; He et al, 2021 ). Moreover, some studies also found that gut microbiota held the potential for individual identification (Wang et al, 2022 ). Moreover, in recent years, the research direction in the field of microbial forensics started to use “marker” as an effective tool.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that gut microbiota can be used to reflect age-related and sex-related changes, helping to roughly identify sexes and different age groups (de la Cuesta-Zuluaga et al, 2019 ; Takagi et al, 2019 ; Huang et al, 2020 ; He et al, 2021 ). Moreover, some studies also found that gut microbiota held the potential for individual identification (Wang et al, 2022 ). Moreover, in recent years, the research direction in the field of microbial forensics started to use “marker” as an effective tool.…”
Section: Discussionmentioning
confidence: 99%
“…And the elevation of Patescibacteria is involved in the process of nerve damage [58]. In another study, the representative gate of increase in the underweight group was Patsciberia, which may affect muscle strength [59]. Actinomyces are one of the four main phyla of intestinal microbiota, and although they account for only a small proportion, they are crucial in maintaining intestinal homeostasis [60].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota is an ecosystem composed of over 35,000 bacterial species, and performs several functions, such as nutrient and drug metabolism and antimicrobial protection, and it is involved in immunomodulation and the integrity of the gut barrier [ 14 ]. Firmicutes and Bacteroidetes constitute 90% of the microbial Phyla that characterize this ecosystem, while the remaining 10% are Actinobacteria , Proteobacteria , Fusobacteria , and Verrucomicrobia [ 15 ]. Specifically, the phylum Firmicutes is further characterized by more than 200 different genera, such as Lactobacillus , Bacillus , Clostridium (with a 95% abundance), Enterococcus , and Ruminicoccus [ 16 ].…”
Section: Gut Microbiota Changes In Mafld Patientsmentioning
confidence: 99%